Toxicity of Proton Therapy versus Photon Therapy on Salvage Re-Irradiation for Non-Small Cell Lung Cancer - Kyungmi Yang; Yang-Gun Suh; Hyunju Shin; Hongryull Pyo; Sung Ho Moon; Yong Chan Ahn; Dongryul Oh; Eunah Chung; Kwanghyun Jo; Jae Myoung Noh (Life, 2022)
This study evaluated the toxicity associated with radiation techniques on curative re-irradiation (re-RT) in patients with thoracic recurrence of non-small cell lung cancer (NSCLC). From 2011 to 2019, we retrospectively reviewed the data of 63 patients with salvage re-RT for in-field or marginal recurrence of NSCLC at two independent institutions. Re-RT techniques using X-ray beams and proton beam therapy (PBT) were also included. Re-RT had a 2-year overall survival (OS) and local progression-free survival of 48.0% and 52.0%, respectively. Fifteen patients experienced grade 3 or higher toxicity after re-RT. The complication rates were 18.2% (4/22) and 26.8% (11/41) in PBT patients and X-ray patients, respectively. Airway or esophageal fistulas occurred in seven patients (11.1%). Fistulas or severe airway obstruction occurred in patients with tumors adjacent to the proximal bronchial tree and esophagus, who underwent hypofractionated radiotherapy (RT) or concurrent chemotherapy, and with a higher dose exposure to the esophagus. In conclusion, salvage re-RT was feasible even in patients with local recurrence within the previous RT field. PBT showed similar survival outcomes and toxicity to those of other techniques. However, thoracic re-RT should be performed carefully considering tumor location and RT regimens such as the fraction size and concurrent chemotherapy.